FPGA-Based Implementation Direct Torque Control of Induction Motor - Saber Krim; Soufien Gdaim; Abdellatif Mtibaa; Mohamed Faouzi Mimouni (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper proposes a digital implementation of the direct torque control (DTC) of an Induction Motor (IM) with an observation strategy on the Field Programmable Gate Array (FPGA). The hardware solution based on the FPGA is caracterised by fast processing speed due to the parallel processing. In this study the FPGA is used to overcome the limitation of the software solutions (Digital Signal Processor (DSP) and Microcontroller). Also, the DTC of IM has many drawbacks such as for example; The open loop pure integration has from the problems of integration especially at the low speed and the variation of the stator resistance due to the temperature. To tackle these problems we use the Sliding Mode Observer (SMO). This observer is used estimate the stator flux, the stator current and the stator resistance. The hardware implementation method is based on Xilinx System Generator (XSG) which a modeling tool developed by Xilinx for the design of implemented systems on FPGA; from the design of the DTC with SMO from XSG we can automatically generate the VHDL code. The model of the DTC with SMO has been designed and simulated using XSG blocks, synthesized with Xilinx ISE 12.4 tool and implemented on Xilinx Virtex-V FPGA.